Effect of Extraction Conditions on Carotenoids from Rhodotorula Mucilaginosa - Khanh Dung Pham; Thi Ngoc Dung Dang; Van Hung Tran (Journal of Technical Education Science, 2024)
Carotenoids are a group of 40-carbon isoprenoids with high lipid solubility, widely found in fruits, vegetables, etc. They have an unsaturated structure with strong antioxidant activity that helps prevent low-density lipoprotein oxidation and protect cells from free radicals. Currently, carotenoids are not only synthesized from natural sources such as plants but also from microorganisms such as bacteria, yeast, algae, etc. One more attention, becoming an important research area, using microorganisms to produce carotenoids has advantages over than plants because it saves costs and can be more easily expanded to an industrial scale. Therefore, in this study, the influence of extraction conditions such as organic acid, ultrasound time, and solvent on the carotenoid extraction from the yeast Rhodotorula mucilaginosa was investigated. The result showed that the process of carotenoid extraction follows 3M citric acid combined with 30 minutes of ultrasound for cell disruption; complete extraction process in 100% ethanol with dry cell weight/ethanol ratio of 1/50 g/mL. The total carotenoid content reached 548.98 ± 6.30 µg/g.